2012
DOI: 10.1182/blood-2011-08-370908
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells orchestrate follicular lymphoma cell niche through the CCL2-dependent recruitment and polarization of monocytes

Abstract: Accumulating evidence indicates that infiltrating stromal cells contribute directly and indirectly to tumor growth in a wide range of cancers. In follicular lymphoma (FL), malignant B cells are found admixed with heterogeneous lymphoid-like stro-mal cells within invaded lymph nodes and BM. In addition, mesenchymal stromal cells (MSCs) support in vitro FL B-cell survival, in particular after their engagement toward lymphoid differentiation. We show here that BM-MSCs obtained from patients with FL (FL-MSCs) disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
149
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(159 citation statements)
references
References 54 publications
(70 reference statements)
9
149
0
1
Order By: Relevance
“…FTH cells are enriched in FL biopsies and secrete cytokines such as IL-4, which binds to the IL-4 receptor on lymphoma cells and triggers signaling by phosphorylation of ERK and STAT6 (78). The role of stromal cells in FL pathogenesis has emerged, as in vitro studies have shown that they increase neoplastic B cell survival, contribute to monocyte recruitment via the secretion of CCL2, and contribute to macrophage polarization (79,80).…”
Section: Microenvironmentmentioning
confidence: 99%
“…FTH cells are enriched in FL biopsies and secrete cytokines such as IL-4, which binds to the IL-4 receptor on lymphoma cells and triggers signaling by phosphorylation of ERK and STAT6 (78). The role of stromal cells in FL pathogenesis has emerged, as in vitro studies have shown that they increase neoplastic B cell survival, contribute to monocyte recruitment via the secretion of CCL2, and contribute to macrophage polarization (79,80).…”
Section: Microenvironmentmentioning
confidence: 99%
“…1) and triggers signaling by phosphorylation of extracellular signal-regulated kinase and STAT6. 57 The role of stromal cells in FL pathogenesis has begun to emerge; in vitro studies have shown that stromal cells increase neoplastic B-cell survival, contribute to monocyte recruitment via the secretion of CCL2 58,59 (left lower side of the orange open circle of "follicular reticular cell FRC" cell in Fig.1), and contribute to macrophage polarization (the blue open circle of "M2 LAM" on the left lower corner in Fig.1). Data from co-culture experiments with bone marrow-derived mesenchymal stromal cells suggest that the malignant cells induce changes in stromal cells toward lymphoid differentiation and overexpression of CCL2, which in turn leads to the recruitment of monocytes that are differentiated into a TAM phenotype.…”
Section: Tumor-associated Mast Cellsmentioning
confidence: 99%
“…Data from co-culture experiments with bone marrow-derived mesenchymal stromal cells suggest that the malignant cells induce changes in stromal cells toward lymphoid differentiation and overexpression of CCL2, which in turn leads to the recruitment of monocytes that are differentiated into a TAM phenotype. 59 The localization of CD4 + T cells within neoplastic follicles, unlike their absolute number, was associated with poor survival and rapid transformation. TFH provide survival signals to antigen-selected GC B cells, and help them achieve class-switch recombination and differentiation into antibodysecreting plasma cells.…”
Section: Tumor-associated Mast Cellsmentioning
confidence: 99%
“…In follicular lymphoma, stromal cells derived from mononucleated cells have been shown in vitro to secrete CCL2, thereby recruiting monocytes and differentiating them into a tumor-promoting phenotype. 23 A similar insight into macrophage biology is currently lacking in DLBCL. Another question of interest is whether the observed outcome correlations will hold true for other anti-CD20 antibodies and whether the principle of increased antibody-dependent cellular cytotoxicity/phagocytosis of opsonized tumor cells in the presence of macrophages can be generalized to all malignancies that are amenable to monoclonal antibody-based therapy.…”
mentioning
confidence: 99%